Probiotic Lactobacillus Strains Stimulate the Inflammatory Response and Activate Human Macrophages - L. M. Rocha-Ramírez; R. A. Pérez-Solano; S. L. Castañón-Alonso; S. S. Moreno Guerrero; A. Ramírez Pacheco; M. García Garibay; C. Eslava (Journal of Immunology Research)
Lactobacilli have been shown to promote health functions. In this study, we analyzed the mechanism by which four different strains of probiotics affected innate immunity, such as regulation of ROS, cytokines, phagocytosis, bactericidal activity, signaling by NF-κB pp65, and TLR2 activation. The production of ROS was dependent on the concentration and species of Lactobacillus. The results obtained from the tested strains (Lactobacillus rhamnosus GG, L. rhamnosus KLSD, L. helveticus IMAU70129, and L. casei IMAU60214) showed that strains induced early proinflammatory cytokines such as IL-8,TNF-α, IL-12p70, and IL-6. However, IL-1β expression was induced only by L. helveticus and L. casei strains (after 24 h stimulation). Phagocytosis and bactericidal activity of macrophages against various pathogens, such as S. aureus, S. typhimurium, and E. coli, were increased by pretreatment with Lactobacillus. The nuclear translocation NF-κB pp65 and TLR2-dependent signaling were also increased by treatment with the probiotics. Taken together, the experiments demonstrate that probiotic strains of Lactobacillus exert early immunostimulatory effects that may be directly linked to the initial inflammation of the response of human macrophages.